Separator for power storage device

When manufacturing the microporous film of the partition for the power storage device, specific processes of polypropylene, polyethylene and plasticizer are used, including sheet forming, biaxial stretching, plasticizer extraction, heat treatment and winding, the disadvantages of the raw material mixing and extrusion process are solved, and the circulation and capacity maintenance characteristics of the partition are improved.

CN119764751APending Publication Date: 2025-04-04ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411806612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-04-13
Filing Date
2021-04-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when manufacturing a microporous film of a partition for a power storage device, there are disadvantages in the mixing and extrusion process of raw materials, resulting in an increase in the amount of unmelted substances, which affects the circulation characteristics of the partitions.

Method used

A manufacturing method is adopted, including extruding polypropylene, polyethylene and plasticizer in a sheet form, cooling and curing, flake forming, followed by biaxial stretching, extracting the plasticizer to form a microporous film, and performing heat treatment and winding.

Benefits of technology

By reducing the disadvantages of the raw material mixing and extrusion process, the amount of aggregates and gels in the microporous membrane is reduced, and the circulation characteristics and capacity maintenance characteristics of the separator are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179401810000381
    Figure BDA0005179401810000381
  • Figure BDA0005179401810000382
    Figure BDA0005179401810000382
  • Figure BDA0005179401810000391
    Figure BDA0005179401810000391
Patent Text Reader

Abstract

Provided is a separator for an electricity storage device, which contains a microporous membrane. The microporous membrane contains polyethylene and polypropylene. In X-ray diffraction (XRD) or wide-angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm. The polypropylene contained in the microporous membrane has an isotactic five-unit component fraction (mmmm) of 85.0 mol% to 99.7 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application filed on April 13, 2021, with application number 202180004783.9 and invention name “Method for manufacturing a separator for a power storage device”. Technical Field

[0002] The present invention relates to a separator for an electric storage device and a method for producing the same. Background Art

[0003] Microporous membranes are widely used as microfiltration membranes, fuel cell separators, capacitor separators, base materials for functional membranes for expressing new functions by filling pores with functional materials, and separators for power storage devices or constituent materials thereof.

[0004] Lithium ion secondary batteries (LIB) are widely used in notebook personal computers, portable phones, digital cameras, etc. Among them, as a separator for LIB or its constituent material, for example, a polyolefin microporous membrane is known. Patent Document 1 proposes a method for manufacturing a polyolefin microporous membrane with high strength, high specific surface area, and high pore volume as the target. In Patent Document 1, a polyolefin resin having a weight average molecular weight of more than 500,000 and liquid paraffin are melt-kneaded, and liquid paraffin is extracted from the obtained resin composition to manufacture a polyolefin microporous membrane. Patent Document 2 describes the following method: After a polyolefin resin such as polyethylene and a resin other than polyolefin (such as polyamide) are pre-kneaded and pelletized by an extruder, the pellets are mixed with liquid paraffin and extruded, and the liquid paraffin is extracted to manufacture a microporous membrane. In addition, Patent Documents 3 to 5 describe a method for manufacturing a separator for LIB that includes a conventional manufacturing process for a polyolefin microporous membrane.

[0005] In recent years, research on increasing the capacity and energy density of LIBs has been progressing for long-distance driving of electric vehicles. For example, it is known from Non-Patent Document 1 that the energy density of LIBs can be greatly improved by increasing the nickel content in NMC metal oxides as positive electrode materials, making graphite as negative electrode materials contain silicon at a high concentration, or completely replacing it with silicon.

[0006] On the other hand, it is known from non-patent document 2 that the silicon (containing high concentration) negative electrode accumulates or releases lithium ions during charge and discharge, thereby greatly expanding and shrinking in volume. Furthermore, non-patent document 3 records that when the silicon (containing high concentration) negative electrode expands and shrinks during charge and discharge, gaps can be repeatedly formed around the silicon particles, and solid electrolyte interfaces (SEI) are accumulated in the gaps, so that with long-term cyclic use, the silicon (containing high concentration) negative electrode expands irreversibly. As a result, the separator film is repeatedly subjected to compressive force, and in order to release the force, the pore structure of the film is destroyed (crushed) or irreversibly compressed, thereby ion permeability may be reduced. In particular, for the latter (phenomenon recorded in non-patent document 3), lithium-ion batteries composed of various non-aqueous electrolytes are in principle difficult to suppress the generation of SEI.

[0007] It should be noted that in non-patent document 4, Wu et al. reported the representative concept of Kuhn chain for the three-dimensional configuration of polymer chains. In non-patent document 5, as a study on improving the mechanical properties of resin films using mixed resin systems, it was reported that the mechanical properties were improved by controlling the size of different types of particles dispersed in the resin structure or the distance between particles, and by a dispersed structure exceeding a specific dispersion degree.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2002-088189

[0011] Patent Document 2: Japanese Patent Application Publication No. 2002-226639

[0012] Patent Document 3: International Publication No. 2020 / 067161

[0013] Patent Document 4: Japanese Patent Application Publication No. 2020-092068

[0014] Patent Document 5: International Publication No. 2011 / 118660

[0015] Non-patent literature

[0016] Non-patent literature 1: Chem. Rev. 2018, 118, 11433-11456

[0017] Non-patent document 2: J. Phys. Chem. C 2014, 118, 9395-9399

[0018] Non-patent document 3: ACS Appl. Mater. Interfaces 2019, 11, 45726-45736

[0019] Non-patent document 4: Journal of Polymer Science: Part B: Polymer Physics, Vol. 27, 723-741 (1989)

[0020] Non-patent document 5: POLYMER, 1985, Vol 26, November 1855 Summary of the invention

[0021] Problem that the invention aims to solve

[0022] In recent years, when manufacturing a microporous film as a constituent material of a separator for a power storage device, it is required to reduce the disadvantages of the process of mixing and extruding multiple raw materials (i.e., the amount of unmelted material). The unmelted material during the mixing and extrusion process may cause aggregates, gels, etc. in the final microporous film. It is expected that a power storage device with excellent capacity maintenance characteristics (cycle characteristics) during repeated charge and discharge can be realized by a separator having a microporous film with reduced disadvantages.

[0023] However, the microporous membranes described in Patent Documents 1 and 2 have room for improvement from the perspectives of the shortcomings of the raw material mixing and extrusion process and the cycle characteristics of the power storage device equipped with the separator. In addition, Patent Documents 3 to 5 do not focus on the form of the resin raw material in the melt kneading process or the extrusion process, and do not describe in detail the influence of the type or structure of the polyolefin in the separator for the power storage device on the cycle characteristics.

[0024] In view of the above circumstances, an object of the present invention is to provide a separator for an electricity storage device having reduced disadvantages in the raw material mixing and extrusion process and excellent cycle characteristics.

[0025] Solutions for solving problems

[0026] The present inventors have conducted studies to solve the above problems and have found that the above problems can be solved by using a method for producing a separator for a power storage device having the following technical features, thereby completing the present invention. A part of the embodiments of the present invention are exemplified below.

[0027] [1] A method for manufacturing a separator for a power storage device, comprising the following steps:

[0028] (1) a sheet forming step of extruding polypropylene, polyethylene and a plasticizer in a sheet form by an extruder, cooling and solidifying the sheet form, and processing the sheet form into a sheet-like formed body;

[0029] (2) a stretching step of stretching the sheet-like formed body at a surface ratio of 20 to 250 times to form a stretched product;

[0030] (3) a microporous membrane forming step of extracting the plasticizer from the stretched product to form a microporous membrane;

[0031] (4) a heat treatment step of subjecting the microporous membrane to heat treatment, stretching and relaxing the microporous membrane in the width direction to obtain a heat-treated microporous membrane; and

[0032] (5) a winding step of winding up the heat-treated microporous membrane,

[0033] The polyethylene is in a powdery form, and the polypropylene is in a pelletized form.

[0034] [2] The method for producing a separator for a power storage device according to item 1, wherein the polypropylene and the polyethylene are fed into the extruder by any one of the following methods (a) to (c):

[0035] (a) A method in which the polypropylene and the polyethylene are fed into the extruder using different feeders respectively;

[0036] (b) a method in which the polypropylene and the polyethylene are dry-blended and fed into an extruder using a feeder;

[0037] (c) A method in which a plurality of resin raw materials obtained by dry-blending the polypropylene and the polyethylene are fed into an extruder using different feeders.

[0038] [3] The method for producing a separator for a power storage device according to item 1 or 2, wherein the mass ratio of the polyethylene to the polypropylene is 99 / 1 to 60 / 40.

[0039] [4] The method for producing a separator for a power storage device according to item 3, wherein the weight average molecular weight (Mw) of the polyethylene is 100,000 to 9,700,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 3 to 12.

[0040] [5] The method for producing a separator for a power storage device according to item 3, wherein the weight average molecular weight (Mw) of the polypropylene is 300,000 to 2,000,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 3 to 12, and

[0041] The isotactic pentad fraction (mmmm) of the polypropylene is 85.0 mol% to 99.7 mol%.

[0042] [6] A separator for a power storage device, produced by the production method according to any one of items 1 to 5.

[0043] [7] The separator for a power storage device according to item 6, wherein

[0044] The aforementioned separator for an electricity storage device comprises a microporous membrane,

[0045] The microporous membrane contains polyethylene and polypropylene.

[0046] In the X-ray diffraction (XRD) or wide angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm.

[0047] [8] A separator for an electrical storage device, comprising a microporous film,

[0048] The microporous membrane contains polyethylene and polypropylene.

[0049] In an X-ray diffraction (XRD) measurement of the microporous film, the crystallite size of the polyethylene was 15 nm to 40 nm, and the crystallite size of the polypropylene was 10 nm to 50 nm.

[0050] [9] The separator for a power storage device according to item 8, wherein the crystallinity of the polyethylene is 55% to 99.9% in an XRD measurement of the microporous film.

[0051]

[10] A separator for an electrical storage device, comprising a microporous film,

[0052] The microporous membrane contains polyethylene and polypropylene.

[0053] In wide angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene was 15 nm to 40 nm, and the crystallite size of the polypropylene was 10 nm to 50 nm.

[0054]

[11] The separator for a power storage device according to item 10, wherein the crystallinity of the polyethylene is 50% to 90% in WAXS measurement of the microporous film.

[0055]

[12] The separator for a power storage device according to any one of items 8 to 11, wherein the isotactic pentad fraction (mmmm) of the polypropylene contained in the microporous film is 85.0 mol % to 99.7 mol %.

[0056]

[13] A battery comprising the separator for a power storage device according to any one of items 6 to 12.

[0057] Effects of the Invention

[0058] According to the present invention, a method for producing a microporous membrane or a separator for a power storage device can be provided, in which the disadvantages of the raw material mixing and extrusion process are reduced. In addition, according to the present invention, a power storage device can be provided, in which the amount of aggregates or gel content of the separator for a power storage device obtained by the above-mentioned production method is reduced and the cycle characteristics are excellent. DETAILED DESCRIPTION

[0059] The following describes the embodiments of the present invention, but the present invention is not limited by the following embodiments and can be variously modified within the scope of the subject matter. In this specification, "~" means that the numerical values ​​at both ends are included as the upper limit and lower limit unless otherwise specified. In addition, in this specification, the upper limit and lower limit of the numerical range can be arbitrarily combined.

[0060] The first embodiment of the present invention provides a separator for a power storage device containing a microporous membrane, and a crystal structure of a resin component that specifically constitutes the microporous membrane. The second embodiment of the present invention provides a method for manufacturing a separator for a power storage device containing a microporous membrane, and specific raw materials are used in the manufacturing method. Each embodiment is described below.

[0061] <Separators for power storage devices>

[0062] One aspect of the present invention provides a separator for an electricity storage device. A separator for an electricity storage device (hereinafter sometimes simply referred to as a "separator") is a member that is disposed between a plurality of electrodes in an electricity storage device and has ion permeability and, if necessary, shutdown characteristics.

[0063] The separator can be in the form of a flat film (for example, formed by one microporous film), a laminated film (for example, a laminate of multiple microporous films, a laminate of a microporous film and other films), a coated film (for example, a case where a functional substance is coated on at least one side of a microporous film), etc.

[0064] The separator of the first embodiment has a microporous membrane containing polyethylene (PE) with a crystallite size of 15nm to 40nm and polypropylene (PP) with a crystallite size of 10nm to 50nm. The crystallite size can be measured by a known method, for example, by an X-ray diffraction (XRD) method using a reflection X-ray diffraction device Ultima-IV manufactured by Rigaku Corporation, or by a wide-angle X-ray scattering (WAXS) method using a transmission X-ray scattering device NANOPIX, etc. The constituent elements of the separator are described below.

[0065] <Microporous membrane>

[0066] The microporous membrane can be used as a microfiltration membrane, a separator for a fuel cell, a separator for a capacitor, a separator for an electricity storage device, an electrolytic membrane, or a constituent material thereof.

[0067] When a microporous membrane is used as a separator for a power storage device or a constituent material thereof, in particular, a separator for LIB or a constituent material thereof, the microporous membrane itself can be used as the separator, or another layer or other membrane can be provided on at least one side of the microporous membrane to be used as the separator. The microporous membrane used as a separator for a power storage device is preferably a microporous membrane having low electron conductivity, ion conductivity, high resistance to organic solvents, and fine pore size.

[0068] From the viewpoint of shutdown characteristics when used as a separator for a power storage device, the microporous membrane is preferably formed of polyolefin (PO) at 50% by mass or more and 100% by mass or less, and the PO ratio is more preferably 60% by mass or more and 100% by mass or less, and further preferably 70% by mass or more and 100% by mass or less. From the viewpoint of thermal break resistance and pore size reduction, the microporous membrane preferably contains both polyethylene (PE) and polypropylene (PP) as PO.

[0069] The microporous membrane of the first embodiment contains PE having a crystallite size of 15 nm to 40 nm and PP having a crystallite size of 10 nm to 50 nm, which is considered to mean that a microporous membrane is formed in which the crystal states of PE and PP are appropriately distributed.

[0070] In addition, compared with the separators for silicon (containing high concentration) negative electrodes as described in non-patent documents 1 to 3, the microporous membrane with appropriate crystal distribution of PE and PP is easy to recover the volume in the compression direction by swelling of the electrolyte, for example, it is easy to deform and respond to the expansion and contraction of the negative electrode such as the negative electrode containing silicon (i.e., it is easy to recover even if the pore size of the microporous membrane is reduced), and / or when the negative electrode containing silicon (silicon) shrinks, the separator and the negative electrode are in close contact, so it is not easy to form a gap between the two, and there is a tendency to suppress the deposition and growth of the excessive solid electrolyte interface (SEI) on the surface of the negative electrode, which is considered to improve the cycle during long-term use in the storage device. On the other hand, the appropriate crystal distribution of PE and PP suggests that the disadvantages of the mixing and extrusion process of the resin raw materials in the manufacturing process of the microporous membrane are reduced. From this viewpoint, the combination of crystallite sizes of PE and PP is preferably PE crystallite size of 16 nm to 39 nm and PP crystallite size of 11 nm to 49 nm, more preferably PE crystallite size of 20 nm to 38 nm and PP crystallite size of 11 nm to 47 nm.

[0071] Appropriate crystal distribution of PE and PP in the microporous membrane can be achieved, for example, by specifying the states of PE and PP in the mixing and extrusion process of the resin raw materials or controlling the stereoregular structure such as the isotactic pentad fraction (mmmm) of PP.

[0072] (Polyethylene (PE))

[0073] Polyethylene (PE) preferably has a weight average molecular weight (Mw) of 100,000 to 9,700,000, and / or a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12. Such Mw and Mw / Mn PE resins are also called ultra-high molecular weight polyethylene (UHMWPE), and are preferred from the viewpoints of optimizing the crystal distribution of microporous membranes containing PE and PP, the amount of aggregates and the gel content, and the cycle characteristics of separators and power storage devices using the same.

[0074] From the same viewpoint as above, the Mw of PE is more preferably 120,000 to 9,000,000, and even more preferably 200,000 to 8,500,000. The degree of dispersion (Mw / Mn) thereof is more preferably 4 to 11, and even more preferably 5 to 10.

[0075] For PE alone, from the perspective of the swelling state formed by the electrolyte in the battery, the crystallinity measured by the XRD method is preferably 55% to 99.9%, more preferably 80% to 99.8%, and further preferably 85% to 97%. For PE alone, from the same perspective, the crystallinity measured by the WAXS method is preferably 50% to 90%, more preferably 65% ​​to 80%, and further preferably 68% to 77%. Even if the XRD method and the WAXS method measure the same microporous membrane, there are differences in the measurement results of the crystallite size and crystallinity, and there is a tendency to often find significant differences in the crystallinity measurement. This difference is presumed to be due to the following reasons. The XRD method is a reflection type measurement, which is mainly the measurement result of the information on the surface of the microporous membrane. On the other hand, the WAXS method is a transmission type measurement, which is the measurement result of the averaged information including the surface and internal structure of the microporous membrane. The microporous membrane described in the present specification is subjected to cooling and heating operations from the surface, sheeting, stretching, etc. during the production process, and therefore it is believed that the surface crystallization of the obtained microporous membrane tends to be further advanced.

[0076] For this PE crystal group, it is believed that the overall higher-order structure of the crystal is easy to swell (permeate, internally diffuse) by the thermal energy such as molecular vibration of the electrolyte in the operating temperature range of the battery (-30°C to 80°C), thereby achieving a good volume recovery rate in the compression direction. The swelling of the PE crystal structure is a phenomenon that occurs when the force of the electrolyte penetration is higher than the force based on the entropy elastic energy of the higher-order structure of PE. Therefore, the swelling of the higher-order structure of PE requires improving the force of electrolyte penetration, or constructing a higher-order structure of PE that is easy to swell with the electrolyte (after swelling, the overall higher-order structure is a higher-order structure of PE that can achieve thermal energy stabilization). In the present invention, a higher-order structure of PE that is easy to swell while maintaining the mechanical strength of the microporous membrane within the operating temperature range of the battery can be constructed. According to this tendency, the PE crystallite size is preferably 15nm to 40nm, more preferably 16nm to 39nm, and further preferably 20nm to 38nm. The crystallite size of PE alone can be adjusted within the above numerical range by, for example, controlling the PE form or PE raw material feeding method in the microporous membrane production process, specifying the ratio of PE raw material to polypropylene (PP) raw material, etc.

[0077] PE can be not only a single type, but also can contain multiple types of UHMWPE. From the perspective of high strength of the microporous membrane, UHMWPE is preferably poly(ethylene and / or propylene-co-α-olefin), more preferably at least one selected from the group consisting of poly(ethylene-co-propylene), poly(ethylene-co-butylene) and poly(ethylene-co-propylene-co-butylene). From the same perspective, UHMWPE preferably contains structural units derived from ethylene at 98.5 mol% or more and 100 mol% or less, and more preferably contains structural units derived from α-olefins other than ethylene at more than 0.0 mol% and less than 1.5 mol%.

[0078] PE may contain polyethylene resins other than UHMWPE. Examples of polyethylene resins other than UHMWPE include low-density polyolefins (LDPE) such as linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), high-pressure low-density polyethylene, and mixtures thereof.

[0079] (Polypropylene (PP))

[0080] The polypropylene (PP) preferably has a weight average molecular weight (Mw) of 300,000 to 2,000,000, and a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 3 to 12. Such Mw and Mw / Mn of the PP resin are preferred from the viewpoints of optimizing the crystal distribution of the microporous membrane containing PE and PP, the amount of aggregates and the gel content, and the cycle characteristics of the separator and the power storage device using the same.

[0081] From the same viewpoint as above, the Mw of PP is more preferably 305,000 to 1,900,000, and even more preferably 310,000 to 1,800,000. The degree of dispersion (Mw / Mn) thereof is more preferably 4 to 11, and even more preferably 4.5 to 10.

[0082] For the crystallite size of PP alone, from the perspective of good volume recovery in the compression direction of the microporous membrane containing PE and PP through swelling of the electrolyte in the battery, it is preferably 10nm to 50nm, more preferably 11nm to 49nm, and further preferably 11nm to 47nm. Since PP is incompatible with PE, it will not form mixed crystals with PE, and a mixed crystal system that is finely dispersed in the mesh structure of PE can be constructed. As shown in non-patent document 5, by controlling the size of different types of particles dispersed in the resin structure or the distance between particles, a dispersed structure exceeding a specific dispersion degree may significantly improve mechanical properties such as impact strength. It is known that this phenomenon is controlled by controlling the size of the dispersed different types of particles in the range of hundreds of nm to several μm. In contrast, in the present embodiment, the following surprising discovery is obtained: rather than particles, it is the control of the crystal structure of PE and PP that has not been previously available that can improve the mechanical properties of the volume recovery in the compression direction of the separator at a significantly small order of tens of nm. The crystallite size of PP alone can be adjusted within the above numerical range by, for example, controlling the PP form or the method of charging PP raw materials in the production process of the microporous membrane, specifying the ratio of PP raw materials to polyethylene (PE) raw materials, etc.

[0083] PP is preferably a propylene homopolymer from the viewpoint of heat resistance and melt viscosity. Examples of PP include isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene. Among them, isotactic polypropylene is preferred. The amount of isotactic PP is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 98% by mass or more, and further preferably 100% by mass (total) relative to the total mass of PP in the microporous membrane.

[0084] From the viewpoint of optimizing the crystal distribution of PE and PP in the microporous membrane, the isotactic pentad fraction (mmmm) of the stereoregular structure (pentad sequence) of PP is preferably 85.0 mol% to 99.7 mol%, more preferably 86.0 mol% to 99.6 mol%, and further preferably 87.0 mol% to 99.5 mol%.

[0085] From the viewpoint of optimizing the crystal distribution of PE and PP in the microporous membrane, (mmmr) is preferably 0.5 mol% to 2.5 mol%, more preferably 0.9 mol% to 2.4 mol% in the pentad sequence of PP.

[0086] From the same viewpoint as described above, (rmmr) is preferably 0.1 mol% to 1.0 mol%, more preferably 0.1 mol% to 0.6 mol% in the pentad sequence of PP.

[0087] From the same viewpoint as described above, in the pentad sequence of PP, (mmrr) is preferably 0.3 mol% to 2.5 mol%, more preferably 0.5 mol% to 2.3 mol%.

[0088] From the same viewpoint as described above, in the pentad sequence of PP, (mmrm+rrmr) is preferably 0.5 mol% to 1.5 mol%, more preferably 0.7 mol% to 1.3 mol%.

[0089] From the same viewpoint as above, in the pentad sequence of PP, (mrmr) is preferably 0.5 mol% or less, more preferably 0.4 mol% or less.

[0090] From the same viewpoint as described above, in the pentad sequence of PP, (rrrr) is preferably 0.1 mol% to 1.5 mol%, more preferably 0.2 mol% to 1.2 mol%.

[0091] From the same viewpoint as described above, (rrrm) is preferably 0.1 mol% to 1.5 mol%, more preferably 0.2 mol% to 1.0 mol% in the pentad sequence of PP.

[0092] From the same viewpoint as described above, (mrrm) is preferably 0.1 mol% to 1.5 mol%, more preferably 0.2 mol% to 1.0 mol% in the pentad sequence of PP.

[0093] The structure in which the methyl groups of the polypropylene units are connected in the same direction is known as meso (m), and the structure in which the methyl groups are connected in different directions is known as racemic (r). In the present embodiment, by using PP composed of at least one stereo configuration of mmmm to mrrm with a ratio defined as described above, it is found that the crystal distribution of PE is excellently adjusted in the manufacture of the microporous membrane.

[0094] For this phenomenon, it is important that the dissolved PE and PP are well dispersed at the molecular level under the coexistence of plasticizers, and in particular, it is required to control the mutual entanglement of PP molecular chains. As shown in non-patent document 4, Wu et al. reported that the representative concept of the three-dimensional configuration of polymer chains is the Kuhn chain model, and the three-dimensional configuration of polymer chains is determined by a certain degree of unit bending of the monomer. In the Kuhn chain model, "node" refers to the atom between bonds, and in the case of PP, it refers to C atoms, and "l k" is the bonding length, and in the case of PP it is the distance between C atoms. It can be seen that the three-dimensional angle between the chain segments is obtained based on this model, and a theoretical formula for calculating the distance between the two ends of the polymer chain is derived, so that the structure in which the molecular chains are entangled with each other can be logically described. In this embodiment, the ratio of the mmmm stereo configuration in PP is experimentally determined, and it is estimated that this PP is the rotation radius that shows good dispersibility with PE in the plasticizer.

[0095] (mass ratio of PE to PP)

[0096] For the mass ratio of polyethylene to polypropylene, as the PE / PP mass ratio, it is preferably 99 / 1 to 60 / 40, more preferably 97 / 3 to 70 / 30, further preferably 95 / 5 to 85 / 15, and most preferably 93 / 7 to 90 / 10. When the PE / PP mass ratio in the microporous membrane is adjusted to the above numerical range, it is presumed that PP is uniformly dispersed in PE. In fact, in the manufacturing process of the microporous membrane, it is difficult to uniformly disperse PP in PE when only the PE raw material and the PP raw material are simply mixed. Although it is not desired to be limited by theory, in the manufacturing process of the separator for the storage device described later, for the PE raw material and the PP raw material, by controlling their respective forms or raw material input methods for a special extrusion process, there is a tendency to obtain the above-mentioned suitable dispersion. Thus, according to the above method, it is easy to more appropriately disperse PP in PE at the above-mentioned mass ratio.

[0097] (Other contents)

[0098] The microporous film may contain a polyolefin (PO) resin other than PE and PP, for example, a butene homopolymer having excellent crystallinity, etc., within a range not inhibiting the effect of the present invention.

[0099] In addition, the microporous membrane may contain, as a resin component other than PO, for example, polyamide resins such as nylon 6, nylon 66, nylon 11, nylon 6-10, nylon 6-12, nylon 6-66, and aramid resins, polyimide resins, polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), fluorine resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), copolymers of ethylene and vinyl alcohol (e.g., EVAL manufactured by Kuraray Co., Ltd., melting point: 157°C to 190°C), polysulfone, polyethersulfone, polyketone, polyetheretherketone (PEEK), etc. These resin components may be used alone or in combination.

[0100] The microporous membrane may contain additives other than the resin within the range that does not hinder the effect of the present invention. Examples of additives include dehydration condensation catalysts, metal soaps such as calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, coloring pigments, and the like.

[0101] (Various properties of microporous membranes)

[0102] The characteristics of the microporous membrane are described below.

[0103] These characteristics are for the case where the microporous membrane as the separator for a power storage device is a flat membrane, but when the separator for a power storage device is in the form of a laminated membrane, the layers other than the microporous membrane may be removed from the laminated membrane and then measured.

[0104] The porosity of the microporous membrane is preferably 20% or more, more preferably 30% or more, further preferably 32% or more or 35% or more. When the porosity of the microporous membrane is 20% or more, when the microporous membrane is used as a separator for an alkali metal ion battery or its constituent material, there is a tendency for the rapid migration of alkali metal ions to be further improved. On the other hand, the porosity of the microporous membrane is preferably 90% or less, more preferably 80% or less, and further preferably 50% or less. When the porosity of the microporous membrane is 90% or less, there is a tendency for the membrane strength to be further improved and the self-discharge to be further suppressed. The porosity of the microporous membrane is determined by the method described in the examples.

[0105] Microporous membrane air permeability per 100cm 3 , preferably 1 second or more, more preferably 50 seconds or more, further preferably 55 seconds or more, and further preferably 100 seconds or more. The air permeability of the microporous membrane is 1 second or more, and there is a tendency to further improve the balance of film thickness, porosity and average pore size. In addition, the air permeability of the microporous membrane is preferably 400 seconds or less, more preferably 300 seconds or less. The air permeability of the microporous membrane is 400 seconds or less, and there is a tendency to further improve ion permeability. The air permeability of the microporous membrane can be adjusted by adjusting the stretching ratio, stretching temperature, etc. The above air permeability is measured by the method described in the embodiment.

[0106] The film thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, further preferably 3.0 μm or more, or 4.0 μm or more. When the film thickness of the microporous membrane is 1.0 μm or more, there is a tendency for the film strength to be further improved. In addition, the film thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, further preferably 80 μm or less, 22 μm or less, or 19 μm or less. When the film thickness of the microporous membrane is 500 μm or less, there is a tendency for the ion permeability to be further improved. The film thickness of the microporous membrane can be adjusted by adjusting the stretching ratio, the stretching temperature, etc. The above film thickness is measured by the method described in the embodiment.

[0107] In particular, when a microporous membrane is used as a separator for LIB or its constituent material, the thickness of the microporous membrane is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, and further preferably 18 μm or less. At this time, the thickness of the microporous membrane is 25 μm or less, and there is a tendency for the permeability to be further improved. At this time, the lower limit of the thickness of the microporous membrane can be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.0 μm or more.

[0108] <Method for producing separator for power storage device>

[0109] Another aspect of the present invention provides a method for producing a separator for a power storage device containing a microporous membrane. The method for producing a separator for a power storage device according to the second embodiment may include a method for producing a microporous membrane, comprising the following steps:

[0110] (1) a sheet forming step of extruding pelletized polypropylene (PP), powdered polyethylene (PE) and a plasticizer in a sheet form by an extruder, cooling and solidifying the sheet form, and processing the sheet form into a sheet-like molded body;

[0111] (2) a stretching step of biaxially stretching the sheet-like formed body at a surface ratio of 20 times or more and 250 times or less to form a stretched product;

[0112] (3) a microporous membrane forming step of extracting a plasticizer from the stretched product to form a microporous membrane;

[0113] (4) a heat treatment step of subjecting the microporous membrane to heat treatment, stretching and relaxing the microporous membrane in the width direction (TD) to obtain a heat-treated microporous membrane; and

[0114] (5) A winding step of winding the heat-treated microporous membrane.

[0115] The manufacturing method of the separator for the storage device of the second embodiment can reduce the disadvantages (i.e., the amount of unmelted material) of the mixing and extrusion process of multiple raw materials by forming the PE raw material into powder and the PP raw material into pellets and mixing and extruding them to form a film. The unmelted material during the mixing and extrusion process may cause the aggregates, gels, etc. of the finally obtained microporous film and the separator containing it, so the separator having a microporous film with reduced disadvantages can achieve the thickness maintenance characteristics (cycle characteristics) of the separator during repeated charge and discharge or the capacity maintenance characteristics (cycle characteristics) of the storage device.

[0116] In addition, in the second embodiment, not only can the separator of the first embodiment described above be obtained, but the crystal distribution of PE and PP in the microporous membrane constituting the separator can be optimized as described above, for example, the expansion and contraction of the negative electrode such as the negative electrode containing silicon can be easily deformed to cope with it, thereby also contributing to the close adhesion between the negative electrode and the separator.

[0117] The resin raw materials and additives used in the second embodiment may be the same as the PE, PP, PO, other resins, and additives described above for the first embodiment. In addition, the separator for the storage device manufactured by the manufacturing method of the second embodiment is also preferably provided with a microporous membrane containing PE with a crystallite size of 15nm to 40nm and PP with a crystallite size of 10nm to 50nm, and more preferably, the isotactic pentad fraction (mmmm) of the stereoregular structure of PP is 85.0 mol% to 99.7 mol%. The following is a description of each step of the second embodiment in sequence.

[0118] [Sheet forming step (1)]

[0119] In step (1), a pelletized PP raw material, a powdered PE raw material, and a plasticizer are supplied to an extruder. As described above, the PE raw material and the PP raw material may be the PE and PP described in the first embodiment at a predetermined mass ratio.

[0120] (Polyethylene (PE) raw material)

[0121] From the viewpoint of improving the yield of the raw material mixing and extrusion steps in the manufacturing process of the microporous membrane and from the viewpoint of easily reducing the amount of unmelted material in the obtained microporous membrane, the PE raw material is preferably in the form of a powder, and based on the total mass of the PE used, 2% to 100% by mass of the powder is more preferably used.

[0122] The preferred "powder" as a PE raw material refers to a powder having a number average particle size (Nd 50 ) is 80μm to 180μm, and the volume average particle size (Vd 50) is 120μm~220μm, number particle size distribution (Nd 80 / Nd 20 ) is 1.1 to 4.2, preferably 1.2 to 4.1, and the volume particle size distribution (Vd 80 / Vd 20 ) is 1.1 to 3.3, preferably 1.15 to 3.2, the crystallite size is in the range of 15 nm to 40 nm, the crystallinity is 30% to 99%, preferably 32% to 98%, more preferably 38% to 97.5%, and contains at least one of the following conditions: 50 ), volume average particle size (Vd 50 ), number particle size distribution (Nd 80 / Nd 20 ), volume particle size distribution (Vd 80 / Vd 20 ), crystallite size, crystallinity, etc. can be measured by known methods.

[0123] For example, for the number average particle size (Nd 50 ), volume average particle size (Vd 50 ), number particle size distribution (Nd 80 / Nd 20 ) and volume particle size distribution (Vd 80 / Vd 20 ) can be obtained by using the flow-type image analysis particle size and shape measuring device Particle Insight made by Micromeritics. In addition, for example, the crystallite size and crystallinity can be obtained by using the XRD measurement of the X-ray diffraction device Ultima-IV made by Rigaku Corporation.

[0124] (Polypropylene (PP) raw material)

[0125] From the viewpoint of improving the yield of the raw material mixing and extrusion steps in the manufacturing process of the microporous membrane and from the viewpoint of easily reducing the amount of unmelted material in the obtained microporous membrane, the PP raw material is preferably in the form of pellets, with the total mass of the PP used as a reference, and 2% to 100% by mass being pellets is more preferably used.

[0126] The pelletized PP can be obtained, for example, by drying the polymerized PP powder, extruding it in a strand form using an extruder, and cutting it into pellets after water cooling. In this case, the viscosity average molecular weight (Mv) of the PP powder raw material is preferably 200,000 or more and 1,000,000 or less, more preferably 250,000 or more and 900,000 or less, and further preferably 300,000 or more and 800,000 or less. It should be noted that the Mv of PP can be calculated by measuring the intrinsic viscosity [η] (dl / g) at 135°C in a decalin solvent based on ASTM-D4020 and using the following formula.

[0127] [η] = 1.10 × 10 -4 Mv 0.80

[0128] Here, the "pellets" preferred as PP raw materials refer to the number average particle size (Nd) of the "powder" preferred as PE raw materials. 50 ) and volume average particle size (Vd 50 ) is large, and the maximum length of one side is less than 10 mm and more than 1 mm. The shape of the pellets is not particularly limited, and can be any one of spherical, elliptical and cylindrical. The pellets are obtained by melt-extruding the raw materials with an extruder, cooling them with water or air, adjusting them into a wire shape, and continuously cutting them. The size or specific shape of the pellets can be adjusted, for example, by wire forming or cutting methods.

[0129] (Combination of powdered PE raw material and granular PP raw material)

[0130] By adjusting the PP raw material to the "pellet" form as described above, the swelling rate achieved by the plasticizer can be greatly delayed (that is, it is presumed that the pelletized PP does not substantially swell). It is important not to hinder the swelling of the powdered PE raw material inside the extruder. In addition, in the melting process after the swelling process, from the perspective of uniform melting, the "pellets" preferred as the PP raw material component refer to pellets having a larger crystallite size than the "powder" preferred as the PE raw material component and having the crystallite size of the PP described in the first embodiment.

[0131] In the method for producing pellets, the temperature of the resin extruded in the form of a strand, the cooling temperature during cutting, the stretching speed of the strand compared to extrusion (melt microstretching), the crystallite size of the pellets, the crystallinity, the size and shape of the pellets can be adjusted. 50 ), volume average particle size (Vd 50 ), crystallite size, crystallinity, etc. can be measured by known methods. For example, these number average particle size (Nd 50 ), volume average particle size (Vd 50), crystallite size and crystallinity can be measured by the same method as in the first embodiment. In addition, the size of the pellets can be obtained by measuring the length of one side using a calibrated vernier caliper, for example.

[0132] The mixing of pelletized PP and powdered PE can significantly improve the uniformity of plasticizer swelling in the extruder. This is believed to be because the swelling rate of pellets can be significantly slower than that of powders. Therefore, the pelletized PP does not excessively hinder the swelling of powdered PE, and the pellets themselves do not swell substantially, and are suitably used in subsequent melt kneading. As a result, even in the melt kneading process, it is easy to evenly disperse the PP component in the PE component down to the molecular level.

[0133] (Plasticizer)

[0134] The plasticizer may be a known material as long as it is liquid at a temperature of 20°C to 70°C and has excellent dispersibility in PE or PP. The plasticizer used in step (1) is preferably a non-volatile solvent that can form a uniform solution above the melting point of PE or PP, taking into account the subsequent extraction. Specific examples of non-volatile solvents include hydrocarbons such as liquid paraffin, paraffin, decane and decalin; esters such as dioctyl phthalate and dibutyl phthalate; higher alcohols such as oleyl alcohol and stearyl alcohol, etc. Among them, liquid paraffin is preferred because it has high compatibility with polyethylene, is not prone to interfacial peeling between the resin and the plasticizer even when the molten kneaded product is stretched, and is easy to stretch uniformly.

[0135] (Supply of raw materials to extruder)

[0136] Examples of the extruder include single-screw extruders, twin-screw extruders, and short-shaft extruders with screws, among which a twin-screw extruder is preferred. In step (1), the raw materials are preferably sheared by a continuous mixer, and more preferably, a continuous mixer is installed in the twin-screw extruder.

[0137] The resin raw material and / or plasticizer are preferably supplied to the extruder at a temperature of 25° C. to 80° C., more preferably 30° C. to 76° C., and even more preferably 30° C. to 70° C., from the viewpoint of ensuring appropriate viscosity and ensuring mutual entanglement of polymer chains to a degree that does not cause a decrease in the molecular weight of the resin raw material.

[0138] The PE and PP raw materials are preferably fed into the extruder by any one of the following methods (a) to (c) from the viewpoints of controlling the crystal structure of PE and PP and controlling the swelling of the plasticizer.

[0139] (a) A method of feeding PP pellets and PE powder into an extruder using different feeders;

[0140] (b) A method in which PP pellets and PE powder are dry-blended in a mixed state and fed into an extruder using a feeder;

[0141] (c) A method of dry-blending PP pellets and PE powder to obtain a plurality of resin raw materials, and feeding the plurality of resin raw materials into an extruder using different feeders.

[0142] Since the control of the crystal structure of PE and PP is important when PE and PP are mixed, the present invention effectively utilizes the thermodynamically semi-compatible characteristics of the two and focuses on controlling the dispersion state of PE and PP within the limited residence time in the extruder. From this perspective, the crystal structure of PE and PP is indirectly controlled by controlling the size of the PE and PP (such as powder, pellets, etc.) input. In addition, before PE is melted in the extruder, the swelling of plasticizers such as liquid paraffin (LP) is most important for the uniform dispersion of PE itself (such as the absence of unmelted material or gel). Experiments have found that mixing an excessive amount of PP melt with LP will increase the viscosity or heterogeneity of the plasticizer, thereby hindering the uniform swelling of PE. From the above viewpoints, the PE and PP raw materials are preferably fed into the extruder by any of the above methods (a) to (c).

[0143] In the feeding method (a), PP and PE can be fed into the extruder simultaneously, sequentially or continuously, and preferably are fed into the twin-screw extruder simultaneously. In the feeding methods (b) and (c), PP and PE are fed into the extruder simultaneously.

[0144] In the charging method (c), PP pellets and PE powder may be dry-blended multiple times to obtain multiple resin raw materials, or a dry blend obtained by dry-blending PP pellets and PE powder once may be divided into multiple types to obtain multiple resin raw materials.

[0145] Among the raw material feeding methods (a) to (c), from the perspective of extrusion stability control, a dispersed state in which PE and PP are uniformly dispersed is constructed. From the perspective of separator thickness retention rate and / or battery cell capacity retention rate after a cycle test, (a) and (b) are more preferred, and (b) is further preferred.

[0146] In addition, plasticizer can be supplied to the twin screw extruder together with PE raw material and / or PP raw material, for example. After the plasticizer is supplied to the twin screw extruder together with PE raw material and / or PP raw material, the plasticizer can also be additionally supplied by the same or different feeders. This twin screw extruder usually has an upper section feed port configured on the upstream side and a mid-section feed port configured on the downstream side and the midway of the melt mixing area compared with the feed port. Therefore, after the mixed slurry is supplied by the upper section feed port of the twin screw extruder, the plasticizer can also be additionally supplied by the previous mid-section feed port of the twin screw extruder. Thus, it is easy to adjust the amount ratio of the liquid paraffin extruded by the twin screw extruder in the resin combination to the desired ratio, and in addition, it is easy to adjust the temperature of the resin combination to the desired range. Of course, the first component or the second component can also be supplied by the mid-section feed port.

[0147] The mixed slurry can be prepared using a continuous mixer. The lower limit of the set temperature of the continuous mixer is preferably 25°C or more, more preferably 30°C or more, from the viewpoint of maximally swelling the PE raw material and the plasticizer, and the upper limit is preferably 68°C or less, more preferably 67°C or less, 66°C or less, or 65°C or less, from the viewpoint of melting the resin raw material during mixing.

[0148] The shear rate of the continuous mixer is 100 seconds from the viewpoint of making the resin raw material contact with the plasticizer uniformly and obtaining a dispersion. -1 ~400,000 seconds -1 , preferably 120 seconds -1 ~398000 seconds -1 , more preferably 1000 seconds -1 ~100,000 seconds -1 .

[0149] The residence time in the continuous mixer is 1.0 to 60 seconds, preferably 2.0 to 58 seconds, and more preferably 2.0 to 56 seconds, from the viewpoint of ensuring dispersion of the resin raw material in the plasticizer.

[0150] (Melt Mixing)

[0151] In the process (1), a resin raw material and a plasticizer are melt-kneaded by a twin-screw extruder to manufacture a resin composition. In the second embodiment, as long as the uniformity of the swelling of the resin raw material for the plasticizer is ensured, there is no limitation on the type, time and other conditions of the device used in the melt-kneading. It should be noted that, as required, PO resins other than PE and PP, resin raw materials other than PO, known additives, such as metal soaps such as dehydration condensation catalysts, calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, coloring pigments, etc. can also be put into a twin-screw extruder.

[0152] (Cooling and solidification, sheet forming)

[0153] In step (1), the molten kneaded product is formed into a sheet. As a method for manufacturing a sheet-like formed body, for example, the molten kneaded product is extruded in a sheet form by a T-die, etc., and is cooled to a temperature sufficiently lower than the crystallization temperature of the resin component by contact with a heat conductor, thereby solidifying. As the heat conductor used in cooling and solidification, metals, water, air, plasticizers, etc. can be listed. Among them, metal rollers are preferably used because of their high efficiency in heat conduction. In addition, when the extruded kneaded product is brought into contact with a metal roller, it is preferably clamped by at least one pair of rollers because there is a tendency that the efficiency of heat conduction is further increased, the film strength is increased by sheet orientation, and the surface smoothness of the sheet is also improved. The die lip spacing when the resin composition is extruded in a sheet form from a T-die is preferably 200 μm or more and 3000 μm or less, more preferably 500 μm or more and 2500 μm or less. If the die lip interval is 200 μm or more, the die burn and the like are reduced, and the influence of streaks and defects on the film quality is less, and the risk of film breakage in the subsequent stretching process can be reduced. On the other hand, if the die lip interval is 3000 μm or less, the cooling speed is fast, and the thickness stability of the sheet can be maintained while preventing uneven cooling. In addition, the extruded sheet-like molded body can also be calendered.

[0154] [Stretching process (2)]

[0155] In step (2), the sheet-like formed body obtained in step (1) is stretched at a surface ratio of 20 times or more and 250 times or less. If the surface ratio is 20 times or more, there is a tendency to give sufficient strength to the obtained microporous membrane. On the other hand, if the surface ratio is 250 times or less, there is a tendency to prevent film breakage and obtain high productivity. Step (2) can be performed before the porous body forming step (3) or after step (3) on the porous body. Furthermore, step (2) can also be performed before or after the plasticizer is extracted from the sheet-like formed body.

[0156] As a stretching treatment, from the viewpoint of reducing the film thickness distribution and air permeability distribution in the width direction (TD), biaxial stretching is preferably compared with uniaxial stretching. By stretching the sheet in a biaxial direction at the same time, the number of times the sheet-like formed body is repeatedly cooled and heated in the film-making process is reduced, and the distribution in the width direction becomes good. As a biaxial stretching method, methods such as simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and multiple stretching can be listed. From the viewpoint of improving penetration strength and uniformity of stretching, it is preferably simultaneous biaxial stretching. In addition, from the viewpoint of ease of control of plane orientation, it is preferably sequential biaxial stretching.

[0157] In this specification, simultaneous biaxial stretching refers to a stretching method in which stretching in MD (machine direction in which the microporous membrane is continuously formed) and stretching in TD (direction that crosses the MD of the microporous membrane at an angle of 90°) are simultaneously performed. The stretching ratio in each direction may be different. Sequential biaxial stretching refers to a stretching method in which stretching in MD and TD is performed independently, and when stretching in MD or TD, the other direction is formed into an unrestricted state or a state fixed to a constant length.

[0158] The stretch ratio is preferably in the range of 20 to 200 times in terms of area ratio, more preferably in the range of 25 to 170 times, and further preferably in the range of 30 to 150 times. The stretch ratio in each axial direction is preferably in the range of 2 to 15 times in MD and in the range of 2 to 15 times in TD, more preferably in the range of 3 to 12 times in MD and in the range of 3 to 12 times in TD, and further preferably in the range of 5 to 10 times in MD and in the range of 5 to 10 times in TD.

[0159] The stretching temperature is preferably 90°C to 150°C, more preferably 100°C to 140°C, and further preferably 110°C to 130°C, from the viewpoint of the meltability of the PE / PP raw material and the film-forming property.

[0160] [Microporous membrane forming step (3)]

[0161] In the process (3), a plasticizer is extracted from the resin composition formed in (1) or the stretched material formed in the process (2) to form a microporous membrane. As a method for extracting the plasticizer, a method can be cited in which, for example, the stretched material is immersed in an extraction solvent to extract the plasticizer and is dried. The extraction method can be any one of an intermittent method and a continuous method. In order to suppress the shrinkage of the microporous membrane, it is preferred to limit the end of the sheet-like formed body in a series of processes of dipping and drying. In addition, the plasticizer residue in the microporous membrane is preferably less than 1% by mass relative to the mass of the entire microporous membrane. It should be noted that after the process (3), the plasticizer can also be recovered and reused by operations such as distillation.

[0162] As the extraction solvent, it is preferred to use a solvent that is a poor solvent for PE and PP resins, a good solvent for plasticizers, and has a boiling point lower than the melting point of PE and PP resins. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. It should be noted that these extraction solvents can be recovered and reused by operations such as distillation.

[0163] [Heat treatment step (4)]

[0164] In step (4), for example, after heat-treating the microporous membrane obtained in step (3) at a temperature not higher than the melting point of the microporous membrane, the microporous membrane is stretched to produce a heat-treated microporous membrane.

[0165] For the microporous membrane, from the viewpoint of suppressing shrinkage, a heat treatment with heat setting as the target is implemented. As a method of heat treatment, with the adjustment of physical properties as the purpose, a stretching operation performed in a specified atmosphere, a specified temperature and a specified stretching ratio can be listed, and / or, with the purpose of reducing tensile stress, a relaxation operation performed in a specified atmosphere, a specified temperature and a specified relaxation rate can be listed. The relaxation operation can be performed after the stretching operation. These heat treatments can be performed using a tenter or a roller stretching machine.

[0166] The stretching operation is preferably performed by 1.1 times or more, more preferably by 1.2 times or more, in MD and / or TD of the film from the viewpoint of improving the strength and porosity of the microporous film. The upper limit of the stretching ratio during heat setting is preferably 3.0 times or less, preferably 2.5 times or less, in both MD and TD.

[0167] In addition, the relaxation operation is a shrinking operation on the MD and / or TD of the film. The relaxation rate refers to the value obtained by dividing the size of the film after the relaxation operation by the size of the film before the relaxation operation. It should be noted that, when both MD and TD are relaxed, it is the value obtained by multiplying the relaxation rate of MD by the relaxation rate of TD. The relaxation rate is preferably less than 0.99, more preferably less than 0.95. From the perspective of film quality, the relaxation rate is preferably greater than 0.5. The relaxation operation can be performed in both directions of MD and TD or only in one direction of MD and TD.

[0168] The temperature of the heat treatment including the stretching or relaxation operation is preferably in the range of 100°C to 170°C from the viewpoint of the melting point (hereinafter also referred to as "Tm") of the PE and PP resins. If the temperature of the stretching and relaxation operation is within the above range, it is preferred from the viewpoint of the balance between the reduction of the thermal shrinkage and the porosity. The lower limit of the heat treatment temperature is more preferably 110°C or more, further preferably 115°C or more, and the upper limit is more preferably 160°C or less, further preferably 150°C or less, and further preferably 140°C or less.

[0169] [Coiling process (5)]

[0170] In step (5), the microporous membrane heat-treated in step (4) or the microporous membrane produced by the second embodiment can be wound into a roll using a winder, for example. The obtained roll can be stored until the microporous membrane is used to produce a separator for a power storage device.

[0171] [Other processes]

[0172] The obtained microporous film or roll can be cut by a slitting machine from the viewpoint of handling and storage stability. In addition, the microporous film can be post-treated as follows: hydrophilization treatment using a surfactant, cross-linking treatment using ionizing radiation, etc. The microporous film obtained by steps (1) to (5) can be used as a single-layer separator, or a plurality of microporous films can be stacked, or a microporous film and other films can be stacked, or a functional layer can be provided on the microporous film, or a microporous film can be coated.

[0173] <Electricity storage device>

[0174] The power storage device of other embodiments of the present invention is equipped with a positive electrode, a negative electrode and a separator comprising the microporous membrane described above. As a power storage device, specifically, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel-hydrogen batteries, nickel-cadmium batteries, double-layer capacitors, lithium ion capacitors, redox flow batteries, lithium-sulfur batteries, lithium-air batteries, zinc-air batteries, etc. can be listed. Among them, from the viewpoint of practicality, preferably lithium secondary batteries, lithium ion secondary batteries (LIB), nickel-hydrogen batteries or lithium ion capacitors, more preferably lithium ion secondary batteries. In addition, from the viewpoints of ionic conductivity, charge and discharge characteristics, the above-mentioned battery preferably contains an electrolyte.

[0175] The electrolyte in the battery may contain water, and the water contained in the system after the battery is manufactured may be the water contained in the electrolyte, or the water brought into the components such as the electrode or the separator. The electrolyte may contain a non-aqueous solvent. As the solvent contained in the non-aqueous solvent of this embodiment, alcohols such as methanol and ethanol; aprotic solvents, etc. can be listed. Among them, as the non-aqueous solvent, an aprotic solvent is preferred.

[0176] Examples of the aprotic solvent include cyclic carbonates, fluoroethylene carbonate, lactones, organic compounds having a sulfur atom, chain fluorinated carbonates, cyclic ethers, mononitriles, alkoxy-substituted nitriles, dinitriles, cyclic nitriles, short-chain fatty acid esters, chain ethers, fluorinated ethers, ketones, and compounds in which a part or all of the H atoms of the aprotic solvents are substituted with halogen atoms.

[0177] Examples of the cyclic carbonate include ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate.

[0178] Examples of the fluoroethylene carbonate include 4-fluoro-1,3-dioxolane-2-one, 4,4-difluoro-1,3-dioxolane-2-one, cis-4,5-difluoro-1,3-dioxolane-2-one, trans-4,5-difluoro-1,3-dioxolane-2-one, 4,4,5-trifluoro-1,3-dioxolane-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolane-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolane-2-one.

[0179] Examples of the lactone include γ-butyrolactone, α-methyl-γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone.

[0180] Examples of the organic compound having a sulfur atom include ethylene sulfite, propylene sulfite, butylene sulfite, amylene sulfite, sulfolane, 3-sulfolene, 3-methylsulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propylene 1,3-sultone, dimethyl sulfoxide, tetramethylene sulfoxide, and ethylene glycol sulfite.

[0181] Examples of the chain carbonate include ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, and ethyl propyl carbonate.

[0182] Examples of the cyclic ether include tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, and 1,3-dioxane.

[0183] Examples of the mononitrile include acetonitrile, propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile.

[0184] Examples of the alkoxy-substituted nitrile include methoxyacetonitrile and 3-methoxypropionitrile.

[0185] Examples of the dinitriles include malononitrile, succinonitrile, methylsuccinonitrile, glutaronitrile, 2-methylglutaronitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanononane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, 2,4-dimethylglutaronitrile, and ethylene glycol bis(propionitrile)ether.

[0186] Examples of the cyclic nitrile include benzonitrile and the like.

[0187] Examples of the short-chain fatty acid esters include methyl acetate, methyl propionate, methyl isobutyrate, methyl butyrate, methyl isovalerate, methyl valerate, methyl pivalate, methyl hydrogenated angelate, methyl caproate, ethyl acetate, ethyl propionate, ethyl isobutyrate, ethyl butyrate, ethyl isovalerate, ethyl valerate, ethyl pivalate, ethyl hydrogenated angelate, ethyl caproate, propyl acetate, propyl propionate, propyl isobutyrate, propyl butyrate, propyl isovalerate, propyl valerate, propyl pivalate, propyl hydrogenated angelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, propyl valerate, propyl pivalate, propyl hydrogenated angelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, Isopropyl valerate, isopropyl neopentanoate, isopropyl hydrogenated angelate, isopropyl caproate, butyl acetate, butyl propionate, butyl isobutyrate, butyl butyrate, butyl isovalerate, butyl valerate, butyl neopentanoate, butyl hydrogenated angelate, butyl caproate, isobutyl acetate, isobutyl propionate, isobutyl isobutyrate, isobutyl butyrate, isobutyl isovalerate, isobutyl valerate, isobutyl neopentanoate, isobutyl hydrogenated angelate, isobutyl caproate, tert-butyl acetate, tert-butyl propionate, tert-butyl isobutyrate, tert-butyl butyrate, tert-butyl isovalerate, tert-butyl valerate, tert-butyl neopentanoate, tert-butyl hydrogenated angelate and tert-butyl caproate, etc.

[0188] Examples of the chain ether include dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme.

[0189] Examples of the fluorinated ether include those of the general formula Rf aa -OR bb (Where Rf aa is an alkyl group containing a fluorine atom, and R bb is an organic group which may contain a fluorine atom), etc.

[0190] Examples of the ketone include acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0191] Examples of the compound in which a part or all of the H atoms of the aprotic solvent are substituted with halogen atoms include compounds in which the halogen atom is fluorine.

[0192] Here, as the fluorinated chain carbonate, for example, methyl trifluoroethyl carbonate, trifluorodimethyl carbonate, trifluorodiethyl carbonate, trifluoroethyl methyl carbonate, methyl 2,2-difluoroethyl carbonate, methyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,3,3-tetrafluoropropyl carbonate can be listed. The above-mentioned fluorinated chain carbonate can be represented by the following general formula:

[0193] R cc -OC(O)OR dd

[0194] {In the formula, R cc and R dd is selected from CH3, CH2CH3, CH2CH2CH3, CH(CH3)2 and CH2Rf ee (Where Rf ee is at least one of the group consisting of a group represented by an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted by at least one fluorine atom, and R cc and / or R dd Contains at least one fluorine atom.}

[0195] In addition, examples of fluorinated short-chain fatty acid esters include fluorinated short-chain fatty acid esters represented by 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, and 2,2,3,3-tetrafluoropropyl acetate. The fluorinated short-chain fatty acid ester can be represented by the following general formula:

[0196] R ff -C(O)OR gg

[0197] {In the formula, R ff is selected from CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, CF3CF2H, CFH2, CF2H, CF2Rf hh CFHRf hh and CH2Rf ii At least one of the group consisting of R gg is selected from the group consisting of CH3, CH2CH3, CH2CH2CH3, CH(CH3)2 and CH2Rf ii At least one of the group consisting of hh is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom may be substituted with at least one fluorine atom, Rf ii is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is replaced by at least one fluorine atom, and R ff and / or R gg Contains at least one fluorine atom, R ff In the case of CF2H, Rgg Not CH3}.

[0198] <LIB>

[0199] LIB is a storage battery that uses lithium transition metal oxides such as lithium cobalt oxide and lithium cobalt composite oxide as the positive electrode, carbon materials such as graphite and black lead, or silicon-containing materials as the negative electrode, and an organic solvent containing lithium salts such as LiPF6 as the electrolyte. During the charge and discharge of LIB, ionized Li reciprocates between the electrodes. In addition, since it is necessary to move the ionized Li between the electrodes at a relatively high speed while suppressing the contact between the electrodes, a separator is arranged between the electrodes. From the viewpoint of being closely fitted with the negative electrode without a gap, the separator of the first embodiment or the separator manufactured by the second embodiment preferably has a negative electrode containing silicon (silicon) when the negative electrode of the LIB is.

[0200] Unless otherwise specified, the condition values, physical property values, characteristic values, etc. described above are measured according to the methods described in the following examples. When the separator contains one microporous membrane and other layers, is a coating membrane, or contains multiple microporous membranes, one microporous membrane is removed from the separator, or the coating portion is removed from the separator to measure or evaluate the characteristics of the microporous membrane.

[0201] Example

[0202] The present invention is described in more detail below with reference to Examples and Comparative Examples. However, the present invention is not limited to the following Examples unless the gist of the present invention is exceeded. The physical properties in the Examples were measured by the following methods.

[0203] <Weight average molecular weight (Mw), number average molecular weight (Mn)>

[0204] ALC / GPC 150C (trademark) manufactured by Waters Corporation was used to measure standard polystyrene under the following conditions to prepare a calibration curve. In addition, chromatograms were measured under the same conditions for each of the following polymers, and the weight average molecular weight and number average molecular weight of each polymer were calculated by the following method based on the calibration curve.

[0205] Chromatographic columns: 2 GMH6-HT (trademark) + 2 GMH6-HTL (trademark) manufactured by TOSOH CORPORATION

[0206] Mobile phase: o-dichlorobenzene

[0207] Detector: Differential Refractometer

[0208] Flow rate: 1.0ml / min

[0209] Column temperature: 140°C

[0210] Sample concentration: 0.1wt%

[0211] (Weight average molecular weight and number average molecular weight of polyethylene and polypropylene)

[0212] By multiplying each molecular weight component in the obtained calibration curve by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3) or 0.64 (Q factor of polypropylene / Q factor of polystyrene=26.4 / 41.3), a polyethylene-converted or polypropylene-converted molecular weight distribution curve is obtained, thereby calculating the weight average molecular weight and number average molecular weight.

[0213] <About the number of mmmm pentads in the stereoregular structure>

[0214] The isotactic pentad fraction (mmmm) in the polypropylene component is used as 13 The (mmmm) peak fraction in all absorption peaks of the methyl carbon region measured by C-NMR was obtained. In addition, the signal attribution of the methyl region containing the isotactic pentad was based on A. Zambelli et al. (Macromolecules 8687 (1975). Specifically, the mmmm pentad fraction containing the stereoregular structure of PP in the raw material and the microporous membrane was determined as follows.

[0215] <Regarding the number of mmmm pentads containing a stereoregular structure of PP in the raw material and the microporous film>

[0216] The sample was dissolved in o-dichlorobenzene-d4 at 130°C or higher to a concentration of 10 wt %. 13 C-NMR measurement. The measurement conditions are as follows.

[0217] Device: Bruker Avance NEO 600

[0218] Pulse program: zgpg30

[0219] Pulse waiting time: 5sec

[0220] Sample tube diameter: 5mmφ

[0221] Measuring temperature: 130℃

[0222] 13In the C-NMR spectrum, the mmmm pentad was assigned to 21.8 ppm, and the peaks in the methyl region from 18 ppm to 22 ppm were assigned to mmmm, mmmr, rmmr, mmrr, rmrr, rmrm, mmrm, rrrr, rrrm, and mrrm. The mmmm pentad fraction was calculated by dividing the integral value of the mmmm pentad by the sum of the integral values ​​of these peaks.

[0223] It should be noted that the chemical shift of each stereostructure is

[0224] mmmm 21.8ppm,

[0225] mmmr 21.6ppm,

[0226] rmmr 21.3ppm,

[0227] mmrr 21.0ppm,

[0228] mmrm+rmrr 20.8ppm,

[0229] rmrm 20.6ppm,

[0230] rrrr 20.3ppm,

[0231] rrrm 20.2ppm,

[0232] mrrm 19.9ppm.

[0233] <Film thickness(μm)>

[0234] The thickness of the separator sample was measured using a micro thickness gauge (KBM, manufactured by Toyo Seiki) at room temperature 23° C. and humidity 40%. The thickness was measured using a terminal having a terminal diameter of 5 mmφ and a load of 44 gf.

[0235] <Porosity(%)>

[0236] A 10 cm × 10 cm square sample was cut from the microporous membrane and its volume (cm 3 ) and mass (g), and density (g / cm 3 ), and the porosity was calculated using the following formula.

[0237] Porosity (%) = (volume - mass / density) / volume × 100

[0238] <Air permeability(seconds / 100cm 3 )>

[0239] The air permeability of the polyolefin microporous membrane was measured in an atmosphere of 23°C and 40% humidity using a Gurley densometer G-B2 (trademark) manufactured by Toyo Seiki Co., Ltd. in accordance with JIS P-8117.

[0240] <Crystal structure analysis>

[0241] The crystallite size of the polyolefin (eg, PE, PP, etc.) contained in the separator or the microporous film contained in the separator can be measured by any of reflection X-ray diffraction and transmission wide-angle X-ray scattering.

[0242] (Transmission method wide angle X-ray scattering measurement)

[0243] The crystallite size of polyolefins (e.g., PE, PP, etc.) contained in the separator or in the microporous membrane contained in the separator was measured using a transmission X-ray scattering device NANOPIX manufactured by Rigaku Corporation. Cu-Kα rays were irradiated to the sample, and the scattering was detected by a semiconductor detector Hypix-6000. The measurement was performed under the conditions of a sample-detector distance of 86 mm, an output power of 40 kV, and 30 mA. The optical system used point focusing, and the measurement was performed under the conditions of slit diameters of 1st slit: φ = 0.55 mm, 2nd slit: open, and Guard slit: φ = 0.35 mm.

[0244] Crystallite size (nm) and crystallinity in wide-angle X-ray scattering measurement using the transmission method

[0245] In the case of transmission method wide-angle X-ray scattering measurement, in the X-ray scattering pattern obtained by the two-dimensional detector, when the X-rays irradiated to the sample propagate in a straight line, pass through the sample, and reach the two-dimensional detector at the center, the scattering intensity at the same distance from the center corresponds to the same scattering angle. Therefore, for the measured X-ray scattering pattern, the intensity average (circular average) of each scattering angle is calculated, thereby obtaining a one-dimensional scattering intensity map for the scattering angle 2θ. The obtained one-dimensional map is separated into six peaks within the range of 2θ=10.0° to 2θ=29.0°, namely, the diffraction peak of the orthorhombic crystal (110) plane of polyethylene, the diffraction peak of the orthorhombic crystal (200) plane of polypropylene, the diffraction peak of the α crystal (110) plane of polypropylene, the diffraction peak of the α crystal (040) plane, the diffraction peak of the α crystal (130) plane, and the amorphous peak of polyethylene. The baseline is drawn by connecting 2θ=29.0° with a straight line from 2θ=10.0°. The (110) plane diffraction peak and (200) plane diffraction peak of polyethylene are approximated by the Voigt function, and the (110), (040), (130) plane diffraction peaks of polypropylene and the amorphous peak of polyethylene are approximated by the Gauss function. It should be noted that the peak position of the amorphous peak is fixed at 2θ=19.6°, the half-width at half-maximum is fixed at 6.3°, and the peak position and half-width at half-maximum of the crystalline peak are not particularly fixed for peak separation. The crystallite size is calculated according to the Scherrer formula (the following formula) from the half-width at half-maximum of the (110) plane diffraction peak of polyethylene and the (110) plane diffraction peak of polypropylene calculated by peak separation. It should be noted that the crystallinity can be obtained as a percentage value obtained by dividing the area of ​​the crystalline peak by the sum of the separated crystalline and amorphous peaks.

[0246] D=Kλ / (βcosθ)

[0247] D: Crystallite size (nm)

[0248] K: 0.9 (constant)

[0249] λ: wavelength of X-rays (nm)

[0250] β: (β1 2 -β2 2 ) 0.5

[0251] β1: The half-height full width of the (hkl) peak calculated from the peak separation result (rad)

[0252] β2: Full width at half maximum of the incident beam (rad)

[0253] θ: Bragg angle

[0254] (Reflection X-ray diffraction measurement)

[0255] · Polyolefin crystallite size (nm) and crystallinity measured by reflection X-ray diffraction

[0256] The XRD measurement of polyolefins (such as PE, PP, etc.) contained in the separator was performed using an X-ray diffraction device Ultima-IV manufactured by Rigaku Corporation. Cu-Kα rays were incident on the sample, and the diffracted light was detected using a detector D / tex Ultra manufactured by Rigaku Corporation. The KRD measurement was performed under the conditions of a sample-detector distance of 285 mm, an excitation voltage of 40 kV, and a current of 40 mA. As the optical system, a concentrated optical system was used, and the measurement was performed under the slit conditions of DS=1 / 2°, SS=release, and a longitudinal slit=10 mm.

[0257] ·Analysis in reflection X-ray diffraction measurement

[0258] The case of polyethylene

[0259] The obtained XRD pattern is separated into three peaks, namely, the orthorhombic (110) plane diffraction peak, the orthorhombic (200) plane diffraction peak and the amorphous peak, in the range from 2θ=9.7° to 2θ=29.0°. The crystallite size is calculated from the half-width at half maximum of the (110) plane diffraction peak according to the Scherrer formula (the following formula). The (110) plane diffraction peak and the (200) plane diffraction peak are approximated by the Voigt function, and the amorphous peak is approximated by the Gauss function. It should be noted that the peak position of the amorphous peak is fixed at 2θ=19.6°, the half-width at half maximum is fixed at 6.3°, and the peak position and half-width at half maximum of the crystalline peak are not particularly fixed for peak separation. The crystallite size is calculated from the half-width at half maximum of the (110) plane diffraction peak calculated by peak separation according to the Scherrer formula (the following formula). It should be noted that the crystallinity can be obtained as a percentage value obtained by dividing the area of ​​the crystalline peak by the sum of the separated crystalline and amorphous peaks.

[0260] The case of polypropylene

[0261] The obtained XRD pattern is in the range of 2θ=6° to 2θ=31°. The diffraction peaks originating from the crystal are separated into five peaks of (110), (040), (130), (111) and (13-1) / (041) planes of α crystal (monoclinic), and the diffraction peaks originating from the amorphous are separated into two. The separated diffraction peaks originating from the crystal and the amorphous are approximated by the Gauss function. It should be noted that the two amorphous peaks are fixed for peak separation as described below. Amorphous peak 1 is fixed at 2θ=14.9° and a half-width of 4.7°, and amorphous peak 2 is fixed at 2θ=19.18° and a half-width of 7.0°. The crystallite size is calculated according to the Scherrer formula (the following formula) from the half-width of the (110) plane diffraction peak obtained by peak separation. The degree of crystallinity can be obtained as a percentage value obtained by dividing the area of ​​the crystalline peak by the sum of the separated crystalline and amorphous peaks.

[0262] D(110)=Kλ / (βcosθ)

[0263] D(110): Crystallite size (nm)

[0264] K: 0.9 (constant)

[0265] λ: wavelength of X-rays (nm)

[0266] β: (β1 2 -β2 2 ) 0.5

[0267] β1: The half-height full width of the (hkl) peak calculated from the peak separation result (rad)

[0268] β2: Full width at half maximum of the incident beam (rad)

[0269] θ: Bragg angle

[0270] <Amount of unmelted material in the separator (pieces / 1000m 2 )>

[0271] The amount of unmelted material in the separator was quantified by observing the separator obtained through the film-forming process of the embodiment and the comparative example using a transmission optical microscope, and the area having an area of ​​100 μm in length and 100 μm in width and not less than that through which light does not pass. 2 The number of resin aggregates per separator area.

[0272] <Cycle test (%) test method 1>

[0273] The positive electrode, the negative electrode and the non-aqueous electrolyte solution were prepared by the following steps a to c.

[0274] a. Preparation of positive electrode

[0275] Nickel, manganese, and cobalt composite oxide (NMC) (Ni:Mn:Co = 1:1:1 (element ratio), density 4.70 g / cm 3 ) with a ratio of 90.4 mass %, graphite powder (KS6) (density 2.26 g / cm 3 , number average particle size 6.5 μm) at a ratio of 1.6 mass %, and acetylene black powder (AB) (density 1.95 g / cm 3 , number average particle size 48nm) at a ratio of 3.8% by mass, and polyvinylidene fluoride (PVDF) as a binder (density 1.75g / cm 3) were mixed at a ratio of 4.2 mass %, and they were dispersed in N-methylpyrrolidone (NMP) to make a slurry. The slurry was applied to one side of a 20 μm thick aluminum foil, which became the positive electrode collector, using a die coater, and after drying at 130°C for 3 minutes, it was compressed using a roller press to make a positive electrode. The amount of positive electrode active material applied at this time was 109 g / m 2 .

[0276] b. Preparation of negative electrode

[0277] According to the method described in Non-Patent Document 3, a graphene negative electrode containing 40% silicon was manufactured and supported with a thickness of 3.6 μm on a copper foil with a thickness of 12 μm serving as a negative electrode current collector to produce a negative electrode.

[0278] c. Production of non-aqueous electrolyte

[0279] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio).

[0280] d. Battery production

[0281] The thickness of the microporous film used as a separator is measured according to the method described in the above item <Film thickness (μm)>. Using the positive electrode, negative electrode, non-aqueous electrolyte, and separator (separator of the embodiment or separator of the comparative example) obtained in the above a to c, a laminated secondary battery with a size of 100 mm×60 mm and a capacity of 3 Ah was prepared under the conditions of a current value of 1A (0.3C) and a termination battery voltage of 4.2V and a constant current constant voltage (CCCV) charge for 3 hours.

[0282] e. Cycle test, thickness retention rate (%) and capacity retention rate (%)

[0283] (e1) Pretreatment

[0284] The battery made in the above d. is charged with a constant current to a voltage of 4.2V at a current value of 1 / 3C, and then charged with a constant voltage of 4.2V for 8 hours, and then discharged with a current of 1 / 3C to a termination voltage of 3.0V. Then, after charging with a constant current to a voltage of 4.2V at a current value of 1C, a constant voltage charge of 4.2V is performed for 3 hours, and then a current of 1C is discharged to a termination voltage of 3.0V. Finally, after charging with a constant current to 4.2V at a current value of 1C, a constant voltage charge of 4.2V is performed for 3 hours. It should be noted that 1C represents the current value at which the reference capacity of the battery is discharged in 1 hour.

[0285] (e2) Cycle test

[0286] For the battery that has undergone the above-mentioned (e1) pretreatment, discharge at a discharge current of 1C to a discharge end voltage of 3V at a temperature of 25°C, and then charge at a charge current of 1C to a charge end voltage of 4.2V. This is regarded as one cycle and is repeatedly charged and discharged. And the capacity retention rate after 1000 cycles relative to the initial capacity (capacity of the first cycle) is calculated as a % value by the following formula.

[0287] Evaluation result (%) = 100 × (maintained capacity after 1000 cycles / initial capacity)

[0288] The separator was taken out from the battery after 100 cycles, and its thickness was measured by the method described in the above item <Film thickness (μm)> The thickness retention rate of the separator after 100 cycles was calculated as a % value by the following formula.

[0289] Evaluation result (%) = 100 × (separator thickness after 100 cycles / separator thickness measured in d. above)

[0290] In addition, the thickness of 10 arbitrary places of the separator taken out was measured, and the average value was used.

[0291] <Cycle test (%) test method 2>

[0292] (Battery production)

[0293] a. Preparation of positive electrode

[0294] LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2, carbon black as a conductive aid, and polyvinylidene fluoride solution as a binder were mixed at a solid content mass ratio of 91:5:4, and N-methyl-2-pyrrolidone was added as a dispersion solvent at a solid content of 68% by mass, and further mixed to produce a slurry solution. The slurry solution was applied to both sides of an aluminum foil with a thickness of 15 μm in a manner that a portion of the aluminum foil was exposed, and the solvent was dried and removed to a coating amount of 175 g / m per single side. 2 The density of the positive electrode mixture is 2.8 g / cm 3 The coated portion was rolled using a roll press in a manner of 30 mm×50 mm and cut into pieces including an exposed portion of the aluminum foil to obtain a positive electrode.

[0295] b. Preparation of negative electrode

[0296] Artificial graphite / silicon particles (Elkem, Silgrain e-Si408) as negative electrode active material = 1:1 (mass ratio), styrene-butadiene rubber as a binder and carboxymethyl cellulose aqueous solution, are mixed at a solid content mass ratio of negative electrode active material: styrene-butadiene rubber: carboxymethyl cellulose = 96.4:1.9:1.7, and water as a dispersing solvent is added at a solid content of 50 mass%, and further mixed to produce a slurry solution. The slurry solution is applied to both sides of a copper foil with a thickness of 10 μm in a manner that a portion of the copper foil is exposed, and the solvent is dried and removed to a coating amount of 86 g / m per single side. 2 The density of the negative electrode mixture is 1.45 g / cm 3 The film was rolled using a roll press in a manner of , and then cut into pieces so that the coated portion was 32 mm×52 mm and included the copper foil exposed portion, thereby obtaining a negative electrode.

[0297] c. Production of non-aqueous electrolyte

[0298] LiPF6 as a solute was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio), and vinylene carbonate was further added at 1.0 wt% to prepare a non-aqueous electrolyte solution.

[0299] d.Battery assembly

[0300] While bending a long separator of 55 mm in width so that the active material surfaces of the positive and negative electrodes face each other and are sandwiched between the positive and negative electrodes, a laminate containing 15 negative electrodes on both sides and 14 positive electrodes on both sides is formed. After welding an aluminum lead sheet with a sealant to the exposed portion of the 14 positive aluminum foils of the laminate, and welding a nickel lead sheet with a sealant to the exposed portion of the 15 negative copper foils, insert it into the aluminum laminated outer shell, and laminate and seal the exposed edges of the positive and negative lead sheets and the other two edges, a total of 3 edges. Then, the above-mentioned non-aqueous electrolyte is injected into the outer shell, and then the opening is sealed to make 28 opposed laminated batteries. After the obtained battery is placed at room temperature for 1 day, it is charged to a battery voltage of 4.2V at a constant current of 330mA (0.3C) in an atmosphere of 25°C, and then a constant voltage charge is performed in a manner of maintaining 4.2V, and the initial charge after the battery is made is performed for a total of 8 hours. Next, the battery was discharged at a current value of 330 mA (0.3C) to a battery voltage of 3.0 V.

[0301] (Cycle Characteristics Evaluation)

[0302] The battery obtained in the above "d. Battery Assembly" was charged and discharged for 1000 cycles in an atmosphere of 25°C. For charging, the battery was charged for a total of 3 hours by charging at a constant current of 1A (1.0C) until the battery voltage was 4.2V, and then charging at a constant voltage in a manner to maintain 4.2V. For discharging, the battery was discharged at a current value of 1A (1.0C) to a battery voltage of 3.0V. The capacity retention rate was calculated from the discharge capacity of the 1000th cycle and the discharge capacity of the 1st cycle. When the capacity retention rate is high, it is evaluated to have good cycle characteristics.

[0303] Evaluation result (%) = 100 × (maintained capacity after 1000 cycles / initial capacity)

[0304] The separator was taken out from the battery after 100 cycles, and its thickness was measured by the method described in the above item <Film thickness (μm)> The thickness retention rate of the separator after 100 cycles was calculated as a % value by the following formula.

[0305] Evaluation result (%) = 100 × (separator thickness after 100 cycles / separator thickness measured in d. above)

[0306] In addition, the thickness of 10 arbitrary places of the separator taken out was measured, and the average value was used.

[0307] <Polyethylene (PE) raw materials>

[0308] Polyethylene (PE) shown in Table 1 was prepared.

[0309] <Using polypropylene (PP) raw material>

[0310] Polypropylene (PP) shown in Table 2 or Table 3 was prepared.

[0311] [Example 1]

[0312] PE1 powder and PP1 pellets were supplied to a screw extruder equipped with a manifold (T die head) with a die lip gap of 1500 μm according to the mass ratio described in Table 4 and the feeding method (a) for melt mixing. During the melt mixing, liquid paraffin (kinematic viscosity at 37.78°C: 7.59×10 -5 m 2 / s) is supplied to a twin-screw extruder by an injection nozzle, and further kneading is performed to extrude the resin composition. At this time, liquid paraffin is further injected from the extrusion middle section (middle section feed port of the twin-screw extruder) in such a manner that the amount ratio of liquid paraffin extruded by the twin-screw extruder in the resin composition is 70% by mass and the temperature of the resin composition is 220°C. Next, the extruded resin composition is extruded onto a cooling roller whose surface temperature is controlled at 25°C, and cast, thereby obtaining a sheet-like molded body.

[0313] Next, the sheet-like formed body was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were as described in Table 4, the stretching ratio was 55 times, and the porosity, air permeability, thickness, etc. were adjusted by appropriately adjusting the stretching temperature, heating air volume, etc. It should be noted that the biaxial stretching temperature was set at 126°C.

[0314] Next, the stretched product was immersed in dichloromethane to extract liquid paraffin from the stretched product, thereby forming a microporous membrane.

[0315] Next, in order to perform heat setting of the microporous membrane, it was guided to a TD tenter, heat set (HS) was performed at 129°C, stretched at a TD stretching ratio of 2.0 times, and then relaxed at a rate of 0.9 times in the TD direction (i.e., after stretching 2.0 times in the TD direction, the relaxation operation was performed to 1.8 times relative to before heat setting). The above evaluation of the heat-treated microporous membrane was performed. Then, the above separator evaluation and battery evaluation were performed using the microporous membrane as a separator. The evaluation results are shown in Table 4.

[0316] [Examples 2 to 20 and Comparative Examples 1 to 3]

[0317] Microporous membranes were prepared and evaluated in the same manner as in Example 1 except that the raw material composition, raw material charging method, or stretching ratio in the stretching step were changed as shown in Tables 4 to 6. The evaluation results of the obtained microporous membranes, separators, and batteries are shown in Tables 4 to 6.

[0318] [Table 1]

[0319]

[0320] [Table 2]

[0321]

[0322] [Table 3]

[0323]

[0324] [Table 4]

[0325]

[0326] [Table 5]

[0327]

[0328] [Table 6]

[0329]

[0330] (Explanation of Abbreviations in Tables 4 to 6)

[0331] Raw material feeding method (a): PE and PP are fed into the extruder through different feeders.

[0332] Raw material feeding method (b): A dry blend of PE and PP is fed into the extruder through a feeder.

[0333] Raw material feeding method (c): A plurality of resin raw materials are obtained by dry blending PE and PP, and the obtained plurality of resin raw materials are fed into the extruder through different feeders.

Claims

1. A separator for an electrical storage device, comprising a microporous membrane, The microporous membrane contains polyethylene and polypropylene, In an X-ray diffraction (XRD) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm, The isotactic pentad fraction (mmmm) of the polypropylene contained in the microporous membrane is 85.0 mol % to 99.7 mol %.

2. The separator for an electric storage device according to claim 1, wherein In an X-ray diffraction (XRD) measurement of the microporous film, the crystallite size of the polyethylene is 16 nm to 39 nm, and the crystallite size of the polypropylene is 11 nm to 49 nm.

3. The separator for an electric storage device according to claim 1 or 2, wherein In an X-ray diffraction (XRD) measurement of the microporous film, the crystallite size of the polyethylene is 20 nm to 38 nm, and the crystallite size of the polypropylene is 11 nm to 47 nm.

4. The separator for an electric storage device according to any one of claims 1 to 3, wherein In an XRD measurement of the microporous film, the crystallinity of the polyethylene is 55% to 99.9%.

5. The separator for an electric storage device according to any one of claims 1 to 4, wherein In an XRD measurement of the microporous film, the crystallinity of the polyethylene is 80% to 99.8%.

6. The separator for an electric storage device according to any one of claims 1 to 5, wherein In an XRD measurement of the microporous film, the crystallinity of the polyethylene was 85% to 97%.

7. A separator for an electrical storage device, comprising a microporous membrane, The microporous membrane contains polyethylene and polypropylene, In wide angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 15 nm to 40 nm, and the crystallite size of the polypropylene is 10 nm to 50 nm, The isotactic pentad fraction (mmmm) of the polypropylene contained in the microporous membrane is 85.0 mol % to 99.7 mol %.

8. The separator for an electric storage device according to claim 7, wherein In wide angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 16 nm to 39 nm, and the crystallite size of the polypropylene is 11 nm to 49 nm.

9. The separator for an electric storage device according to claim 7 or 8, wherein In wide angle X-ray scattering (WAXS) measurement of the microporous film, the crystallite size of the polyethylene is 20 nm to 38 nm, and the crystallite size of the polypropylene is 11 nm to 47 nm.

10. The separator for an electric storage device according to any one of claims 7 to 9, wherein In WAXS measurement of the microporous film, the crystallinity of the polyethylene is 50% to 90%.

11. The separator for an electric storage device according to any one of claims 7 to 10, wherein In WAXS measurement of the microporous film, the crystallinity of the polyethylene was 65% to 80%.

12. The separator for an electric storage device according to any one of claims 7 to 11, wherein In WAXS measurement of the microporous film, the crystallinity of the polyethylene was 68% to 77%.

13. The separator for an electric storage device according to any one of claims 1 to 12, wherein The isotactic pentad fraction (mmmm) of the polypropylene contained in the microporous membrane is 86.0 mol % to 99.6 mol %.

14. The separator for an electric storage device according to any one of claims 1 to 13, wherein The isotactic pentad fraction (mmmm) of the polypropylene contained in the microporous membrane is 87.0 mol % to 99.5 mol %. 15 . A battery comprising the separator for an electrical storage device according to claim 1 .

Citation Information

Patent Citations

  • Method for producing porous film

    JP2002088189A

  • Microporous membrane and lithium battery separator

    JP2002226639A

  • Method for producing microporous film

    JP2020092068A

  • Microporous polyolefin film, separator for non-aqueous secondary battery, non-aqueous secondary battery, and process for production of microporous polyolefin film

    WO2011118660A1

  • High-strength separator

    WO2020067161A1